Solid-Liquid Extraction of Heavy Metals in Aqueous Solutions using Chelating Ligands Anchored on Solid Supports - (:unkn) unknown (Ian Tharau Kabogo, 2024)
The rapid surge of population growth has translated to an unprecedented increase in heavy metal pollution in the environment resulting from various anthropogenic activities. Their non-biodegradable nature, toxicity and persistence in the environment raise a lot of concern. There are various methods for heavy metal removal that have been applied as a means of remediation such as adsorption, chelation, chemical precipitation, and ion exchange among others. These methods, however, pose several disadvantages such as difficulty in treatment of toxic sludge generated and high cost of operation. However, solid-phase chelation removal technique despite not being as widely documented as other methods has been found to be very promising in the effort of remediating polluted environmental components as it averts demerits such as waste generation and poor selectivity. In the effort of designing novel compounds which will be instrumental in the remediation of heavy metal polluted environmental components, Schiff base chelating ligands (E)-2-(3,3-dimethoxy-2-oxa-7,10-diaza-3-silaundec-10-en-11-yl)phenol (L1), (E)-N-(2-((pyridine-2ylmethylene)amino)ethyl)-3-(trimethoxysilyl)propan-1-amine (L2) and (E)-N-(2-((thiophen-2-ylmethylene)amino)ethyl)-3-(trimethoxysilyl)propan-1-amine (L3) were immobilized onto SBA-15 mesoporous silica and Fe₃O₄ magnetic nanoparticles to yield their corresponding adsorbents. The synthesized materials were characterized by a wide array of techniques that included NMR, FT-IR, BET/BHJ, TEM, and SEM. The adsorbents were then used for the solid-liquid removal of Cr(VI), Cd(II) and Pb(II) from aqueous solutions. Various physicochemical parameters were varied during the removal studies where the adsorbents recorded relatively high removal efficiencies of the metal cations ranging from 20-68% for Cr(VI), 48-90% for Cd(II) and 62-99% for Pb(II) which varied significantly (p<0.05) between the two adsorbents. Additionally, the nature of adsorption was evaluated using several adsorption isotherms and kinetic models where the Langmuir isotherm model and pseudo-second-order kinetic model yielded the highest correlation coefficients (R²>0.98) that confirmed the role of chemisorption and monolayer adsorption in the removal experiments. The Hard Soft Acid Base (HSAB) theory of metal-ligand interaction was also observed to influence the removal capability of the Schiff bases immobilized adsorbents. Therefore, the Schiff base chelating ligands immobilized onto SBA-15 and Fe₃O₄ magnetic nanoparticles can be synthesized as potential adsorbents for heavy metal removal from aqueous solutions and they can be used as potential sequestering agents for heavy metal cations in wastewater.
Thesis